KOSA KATA BAHASA BALI SERAPAN PADA NOVEL SING JODOH KARYA I MADE SUGIANTO - Bipatrawan, I Gede Arya; Jendra, I Made Iwan Indrawan; Ranem, I Nyoman (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Balinese literature as a means of communication in a variety of written and spoken languages. One of the new Balinese literatures in written form in the form of prose is the novel. In making a novel, what must be considered is the grammatical structure of language such as: phonemes, morphemes, words, clauses, and sentences used by the author so that they are easy to understand. There are also vocabularies from outside Bali or absorption vocabularies used in making novels. One of the novels in which there is absorption vocabulary is the novel entitled Sing Jodoh by I Madé Sugianto. Based on the above background, the writer is interested in researching (1) the borrowed Balinese vocabulary used in the novel Sing Jodoh based on the origin of the source language and the theory used in this study is borrowed theory. This type of research is qualitative, qualitative descriptive approach. Sources of data from the main data and complementary data collected by library methods and reading, note-taking, listening techniques. The data analysis method used is data reduction, data display and conclusion drawing. The results of the data in this study found several loanwords originating from loanword sources, such as: Arabic, Dutch, Indonesian, English, Portuguese, Sanskrit, etc.